ASSET MANAGEMENT ANALYSIS AFTER EXPANSION BAUBAU CITY - Tasdik, Moh.; *, Haselman; Lambali, Suryadi; Ahmad, Badu (IJRDO - Journal of Applied Management Science, 2015)
The research objective was to analyze the impact of regional asset management policy on regional expansion Baubau City. This research was conducted in the City Baubau Southeast Sulawesi Province. The research approach using qualitative research with quasi experimental method. Data collection technique used observation and interviews. Analysis of data through data reduction, data presentation and verification. The results showed that as a result of regional expansion that is less prepared and driven by the interests of power politics and temporary, then the regional division of Baubau impact expansion policy is problematic, especially in the asset management area that is less expensive inventory of assets, legal, audit, asset valuation, asset optimization as well as the supervision and control of assets that make it an Baubau City government has not entirely been handed over by the government Buton as a parent. This is because, due to the impact of a less expensive expansion of asset management application area before doing the division.